Strengthening the financial intermediary role of Islamic banks through sustainable development goals - Mohd. Zain, Nor Razinah; Hassan, Rusni; Salman, Syed Ahmad (International Business Information Management Association, IBIMA, 2019)
Islamic banks have developed into a competitive type of intermediation with quite a few well-known conventional players currently entering the Islamic finance industry, ensuing in additional diverse Islamic financial institutions with a wide variety of product range. This research stands with two main objectives that look into (i) the relevancy of Sustainable Development Goals (SDGs) in Islamic financial services industry (IFSI), with a special focus on the financial intermediary roles of Islamic banks, and (ii) the positive impacts of Sustainable Development Goals (SDGs) in expanding the financial intermediary roles of Islamic banks. After the discussion on the United Nations’ SDGs, the financial intermediary role of Islamic banks is discussed. The researchers found that the SDGs in Islamic banks are closely related to their faith-based principles that closely related to prohibition of interest, excessive ambiguity, and gambling. It is recommended for Islamic banks to implement SDGs in their policies and to make transparent reports on their activities.